Strategies for Engineering High‐Performance PGM‐Free Catalysts toward Oxygen Reduction and Evolution Reactions. Issue 6 (9th March 2020) - Du, Lei; Xing, Lixin; Zhang, Gaixia; Dubois, Marc; Sun, Shuhui
Abstract: The worldwide fossil fuel shortage and resultant environmental issues urgently require renewable and clean energy technologies. Electrocatalytic oxygen reduction/evolution reactions (ORR/OER) are the cornerstone for renewable energy conversion and storage devices, such as fuel cells, electrolyzers, unitized regenerative fuel cells, and metal‐air batteries. High‐performance electrocatalysts are required to improve the ORR and OER activity and stability, and thus the device performance. Therefore, appropriate strategies and methods are crucial for the rational design and synthesis of highly efficient ORR/OER electrocatalysts. On the other hand, the conventional platinum‐group‐metal‐based (PGM‐based) catalysts, such as Pt and Ir/Ru (oxides), have been facing great challenges, including limited resources and high cost, leading to them being less competitive in the market. Thus, a lot of effort has been devoted to developing alternative PGM‐free ORR/OER catalysts, which, however, still suffer from low activity and insufficient stability. In this review paper, the strategies for engineering high‐performance PGM‐free ORR and OER electrocatalysts are discussed by reviewing the most recent advances. At the end, perspectives on the methods to rationally design PGM‐free ORR and OER catalysts are provided. Abstract : Oxygen reduction and evolution reactions (ORR and OER) play key roles in renewable energy devices, which, however, require abundant costly platinum‐group‐metal‐based (PGM‐based) catalysts. The emerging PGM‐free catalysts are promising to address the cost challenge and build a sustainable society. Herein, the strategies for engineering high‐performance PGM‐free ORR/OER catalysts are discussed in terms of active site identification, engineering, and stabilization.